20 Munute Manager: Runing Virtual Meetings - Harvad Business Review (Harvard Business Rewiew Press, 2016)
There are the problems you face daily as your work with people in defferent cities and countries. But you can prepare for and lead a productive meeting from afar. With guiding principles and tips for making your virtual meeting every item on your agenda. This book walks you to through the basic of : - Selecting the right channel your virtual meeting. - Coordinationg the technology that will allow everyone to connect. - Giving your colleagues the materials they need to meaningfully participate from afar. - Keeping participants engaged in the conversation, and bridging the in-person-versus-remote gap. - Assigning and clarifying meeting roles to keep things running smoothly. - Ending with a clear commitment to action for the whole group. - Holding participants accountable, whether they're in the office next door or on the other side of the globe